Derivación de los valores económicos de la producción de leche de bovinos en la parroquia Cusubamba en el cantón Salcedo utilizando funciones de beneficio. - Avila Toapanta, Diego Rafael (2022)
The general objective of this project is economic derivation values of bovine milk production in Cusubamba parish, Salcedo canton, using benefit functions, in order to be able to satisfy needs internal and external control of sale, production and derivatives of the cow within the parish and its different communities. Allowing to establish information to understand the benefit that exists in milk sale in a more timely manner in terms of improving production. In order to know the real situation, quantitative research was used, with a deductive approach, with the support techniques and instruments to collect information, such as direct observation form, evidencing economic activities, bovine metric tape to obtain weight, lactodensimeter for milk density, mastitis test using California Mastitis test (CMT) and statistical software R Studio (R software Core Team 2022) to obtain at production cost tables. The results showed that 50% of the producers in the area participated at present project. 100% of the producers did not have productive and reproductive records. 100% of the producers did not carry out or did not have the knowledge to make production costs. On the other hand, milk density of the majority (91 % of the cows with an average of 1027 g/ml) did not meet established parameters (1028 to 1033 g/ml), leading to a deficiency of fat in the milk. The majority with 87.6 % of the cows had a low number of somatic cells in CMT test, evidencing a good milking management. Therefore, this work proved that 100 % of the producers do not have an adequate management of milk production system, but this project provides a basis for defining genetic selection criteria related to economic utility of cattle production systems in order to select cattle with the highest productivity